Dowell Myers, Immigrantes and Boomers. Forging a NewSocial Contract for the Future of America, Russell Sage Foundation, New York, 2007 - Anguiano Téllez, María Eugenia (Empiria. Revista de metodología de ciencias sociales, 2010)
-